Metabolic features of qualified academic woman rowing in the boat and on the rowing machines - Kvashuk, P. V.; Voronov, A. V.; Ryzhikova, N. V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify the features of metabolic support for rowing by qualified academic women in a boat and on rowing ergometers, taking into account the pace of exercises.